EARLY HIV DETECTION: A DESCRIPTIVE STUDY USING RAPID DIAGNOSTIC TESTS AT THE MARINA PERMAI COMMUNITY HEALTH CENTER - Al Hidayani; Clariza Florence (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Early HIV detection is a key strategy in control HIV/AIDS epidemic in Indonesia. Research This aim For analyze effectiveness of the Rapid Diagnostic Test (RDT) as method detection early HIV in the workplace Marina Permai Community Health Center 2025. Research​ use design descriptive with total sample of 58 people who did HIV test . Examination done use Three immunochromatographic RDT strategies : ViroCheck ® HIV 1/2, Arkan Medical One Step Anti-HIV (1/2), and d3TEKS1 HIV 1/2 Antibody Rapid Test. Research results show that Of the 58 respondents , 5 people (9%) indicated results reactive and 53 people (91%) non- reactive . Based on characteristics demographics , cases reactive found in 3 women (5%), 2 men (3%), with distribution largest in the group aged 18–59 years (4 people, 7%) and 1 case (2%) in the group aged 0–5 years . This study conclude that immunochromatographic RDT effective as tool detection early HIV at the level service primary health with sensitivity and specificity high . Findings This support use of RDT as screening beginning in HIV prevention and control programs in facilities health community . Keywords: Early HIV Detection, Rapid Diagnostic Test, Marina Permai Health Center